Macro Study of Spatial Development Area on Tourism Village - Widhianthini, Widhianthini (JEJAK: Jurnal Ekonomi dan Kebijakan, 2016)
Macro study is one approach that combines the rational method based on the results of previous studies by the authority with the empirical method utilizing the survey techniques. The purpose of this macro study is to identify and analyze the potentials, problems, and the limiting factors, and the needs of the regency; and to recommend the programs and models required by the community to achieve the sustainable development. This research uses the Participatory Rural Appraisal method, theÂ  interview techniques (Semi Structured Interview), the technique of focused group discussion (FGD), the Rapid District Appraisal (RDA), then it is analyzed by the empirical and dynamical systems. The overview of macro studies is particularly relevant in developing the regions, especially the rural areas, based on the existing advantages, such as in Tabanan Regency. Tabanan Regency is a granary in Bali Province and the zoning of agricultural commodities in quadrant III,which is the rural farming area with combined functions between the cultivated and rural areas supported by the tourism department. The studies of the areas in the form of potential analysis, problem analysis, requirement analysis become the guidelines for preparing the development scenarios and program formats. The studies will then constitute the factors driving the realization of sustainable development of tourism villages in supporting the sustainable agriculture.